THE FAST ALGORITHM FOR CAR LICENSE PLATE RECOGNITION (Perner's Contacts, 2009)
In this paper is presented a detection method for the car license plate detection and recognition. The described car detection algorithm is an integral part of systems for car traveling speed measuring and electronic toll gateways. The algorithm was developed regarding to the possibility of easy implementation to embedded systems, especially with low‑leved programing languages. Presented algorithm is very fast and transparent.
Keywords: image processing; car license plate recognition; optical chars recognition